Cardiac haemangioma associated with a duct-dependent congenital heart disease in a newborn infant. (12th January 2017) - Djordjevic, Stefan A.; Glumac, Sofija; Kalanj, Jasna
Abstract: Cardiac haemangiomas are exceedingly rare; however, they can cause significant haemodynamic impairment and disturbances in heart rhythm. Rarely, cardiac tumours may also coexist with congenital heart lesions. We present an extremely unusual case of a cardiac haemangioma in the setting of complex transposition of the great arteries that caused functional tricuspid atresia. To our knowledge, this is the first such case described in the literature.